Anxiety Reviewed from the Perspective of Emotional Regulation in Students Writing Their Theses - Sipayung, Apriana Evita Pricilya; Sinaga, Enzelin Yulia Betrik; Sinuhaji, Edward Aginta; Mirza, Rina; Putra, Achmad Irvan Dwi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
A thesis is a final assignment that must be written by students to complete their study program. In writing a thesis, many students experience anxiety, both during guidance and when faced with the repeated revision process. Excessive anxiety can prevent students from completing their thesis on time. One factor that causes anxiety is students' emotional regulation. With good emotional regulation, students can overcome their anxiety appropriately. The purpose of this study was to assess the relationship between anxiety and emotional regulation in students who are writing a thesis. The hypothesis is